2005
DOI: 10.1002/adem.200500052
|View full text |Cite
|
Sign up to set email alerts
|

Thermoplastic Extrusion to Highly‐Loaded Thin Green Fibres Containing Pb(Zr,Ti)O3

Abstract: textile fabrics, when water droplets are sucked in, a capillary rise test was performed. [16,20] Vertically hanging strips of a textile are immersed with the lower end into a liquid and the rise of the liquid within the textile is observed. Using Washburn's equation the apparent static contact angle within the textile structure can then be obtained by cosh H eq R S rg 2c (1) with the gravitational constant g, the density r and the surface tension c of the liquid. [21] Assuming a complete wetting (cos h = 1) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 11 publications
1
26
0
1
Order By: Relevance
“…3 The thermoplastic binder was chosen based on previous work. 18 The density values were obtained using a helium pycnometer (Micromeritics, AccuPyc 1330).…”
Section: Methodsmentioning
confidence: 99%
“…3 The thermoplastic binder was chosen based on previous work. 18 The density values were obtained using a helium pycnometer (Micromeritics, AccuPyc 1330).…”
Section: Methodsmentioning
confidence: 99%
“…Baixos valores de torque são geralmente requeridos durante a extrusão de feedstocks cerâmicos a fim de evitar uma possível separação das fases pó-ligante. Estudos anteriores com termoplásticos hidrofílicos (como poliamida e polimetilmetacrilato) reportaram a ineficiência destes materiais na formulação de feedstocks em virtude da sua decomposição sob condições de alta temperatura e/ou elevado cisalhamento [23] .…”
Section: Amostra Processamento Em Câmara De Misturaunclassified
“…significantly reduced dust formation during the kneading process). J. Heiber et al also showed that feedstock properties could be improved using pre-coated powders [19]. Measurements of the particle size distribution (PSD) were undertaken using a particle size analyzer (LS 13320, Beckman coulter, Inc, USA).…”
Section: Raw Materialsmentioning
confidence: 99%